Youth leaving foster care : a developmental, relationship-based approach to practice - Smith, Wendy Benjamin, 1946- (New York ; Oxford : Oxford University Press, 2011)
This comprehensive text focuses on youth emerging from care, offering a new theoretical framework to guide students, practitioners, administrators, and policymakers. The book features case vignettes, recommendations for practice and programmes, and a multidimensional perspective on the effects of maltreatment on development, and common mental health disorders and treatment.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Foster children -- Services for -- United States; Foster children -- Psychology; Foster children -- Counseling of; Foster children -- Family relationships -- United States; Foster children -- Deinstitutionalization -- United States; Ex-foster children -- United States -- Social conditions; Ex-foster children -- Education -- United States; Foster children -- Government policy -- United States